AIChE equipment testing procedure. a guide to performance evaluation (Wiley-AIChE, 2014)
"Provides a cost-effective and reliable reference for improving the performance of new and existing process equipment Step-by-step procedures are flexible enough to be applied in a number of industrial applications "--